2001
DOI: 10.1172/jci13077
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-specific loss of murine thrombomodulin disrupts the protein C anticoagulant pathway and causes juvenile-onset thrombosis

Abstract: The thrombomodulin (TM) gene was ablated in mice in a cell type-restricted manner from vascular endothelium by Cre-recombinase-mediated excision controlled by the endothelial cell lineage-specific Tie2 promoter. Forty percent of mutant (TMLox-) mice display a distinct lethal embryonic phenotype not observed in completely TM-deficient embryos. The remaining 60% of TMLox mice survive beyond birth, but invariably succumb to a severe hypercoagulable state and massive thrombosis after 3 weeks, terminating in a leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 47 publications
2
68
0
Order By: Relevance
“…In particular, PECAM-1 expression over struts in 14-and 28-day SES and PES was generally poor, suggesting an inhibition of endothelial cell migration and proliferation, endothelial injury, and/or increased cell turnover. The expression of TM, a physiologically relevant regulator of platelets and coagulation, was also examined because the loss of TM function causes spontaneous thrombosis in the arterial and venous circulation (32). Overall staining for TM was absent or only weakly expressed in 14-and 28-day DES, and was even reduced in ML Vision control stents compared with nonstented segments.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PECAM-1 expression over struts in 14-and 28-day SES and PES was generally poor, suggesting an inhibition of endothelial cell migration and proliferation, endothelial injury, and/or increased cell turnover. The expression of TM, a physiologically relevant regulator of platelets and coagulation, was also examined because the loss of TM function causes spontaneous thrombosis in the arterial and venous circulation (32). Overall staining for TM was absent or only weakly expressed in 14-and 28-day DES, and was even reduced in ML Vision control stents compared with nonstented segments.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, when apo A1 concentration in plasma is decreased, this may potentially result in an impaired hemostatic balance and, thereby an increased tendency for thrombosis. Previous studies have shown that defects in the protein C pathway may, indeed, result in BCS, both in an experimental animal model [30] and in humans [5]. Another potential mode of action, recently published by Dahlbäck and colleagues, is that anionic phospholipids lose their procoagulant properties when incorporated into HDL [31].…”
Section: Discussionmentioning
confidence: 99%
“…Temporal, spatial, and cell type-specific control of Cre-mediated DNA recombination has been reported [24]. In particular, cardiac myocyte-specific [39] or endothelium-specific [40] recombination has been demonstrated using Cre cDNA, which is controlled by either cardiac-specific a-myosin heavy chain promoter or endothelial cell lineage-specific Tie2 promoter, respectively. Moreover, utilizing the cardiac-specific gene recombination system, the function of GATA4 gene [41] and serum response factor gene [39] required for cardiac development have recently been revealed.…”
Section: Discussionmentioning
confidence: 99%